2018
DOI: 10.1016/j.athoracsur.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Repair of Pectus Carinatum

Abstract: Minimally invasive repair of pectus carinatum with the technically modified fourth-generation bar and its securing system has advantages of low morbidity, short hospital stay, and excellent cosmetic results, even in asymmetric cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 23 publications
0
21
0
4
Order By: Relevance
“…In the present case, the severity of the chest wall deformity precluded any minimally invasive or conservative approaches . Furthermore, it required a double osteotomy of the sternum, while usually, a single osteotomy is required, and more extensive chondrotomies, up to the second rib …”
mentioning
confidence: 79%
“…In the present case, the severity of the chest wall deformity precluded any minimally invasive or conservative approaches . Furthermore, it required a double osteotomy of the sternum, while usually, a single osteotomy is required, and more extensive chondrotomies, up to the second rib …”
mentioning
confidence: 79%
“…8). In 2018, Yüksel et al [28] reported his experience with 172 patients over 10 years, and four generations of chest bars, with excellent results in 93.8% of the cases.…”
Section: Non-resective Techniquesmentioning
confidence: 99%
“…10,11 Also the MIRPC procedure performed by experienced surgeons provides excellent results, but side effects and complications have to be noticed. [12][13][14][15] In many cases of CWD patients, the degree of pectus deformity does not immediately warrant surgery, yet patients may benefit from some type of nonsurgical treatment. Other patients are reluctant to undergo surgery because of the pain associated with postoperative recovery and the risk of imperfect results.…”
Section: Introductionmentioning
confidence: 99%